If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 3 + -5 = x + -1(x + 1) Reorder the terms: 3 + -5 + 12x = x + -1(x + 1) Combine like terms: 3 + -5 = -2 -2 + 12x = x + -1(x + 1) Reorder the terms: -2 + 12x = x + -1(1 + x) -2 + 12x = x + (1 * -1 + x * -1) -2 + 12x = x + (-1 + -1x) Reorder the terms: -2 + 12x = -1 + x + -1x Combine like terms: x + -1x = 0 -2 + 12x = -1 + 0 -2 + 12x = -1 Solving -2 + 12x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 12x = -1 + 2 Combine like terms: -2 + 2 = 0 0 + 12x = -1 + 2 12x = -1 + 2 Combine like terms: -1 + 2 = 1 12x = 1 Divide each side by '12'. x = 0.08333333333 Simplifying x = 0.08333333333
| (x+5)(2x-10)=180 | | 7+85=197 | | (2x-1)+(3y+2)i=5-4i | | 8(3x+8+2y)=24 | | 16=8-x+5 | | 3x-6+x+2+2x=180 | | 4X+6=2(X+3)+2 | | a^2-10ab-39b^2=0 | | 6x+(-30x)=72 | | h=-16t^2+48t+1408 | | 6+2x-3=21x+9 | | 79=49-y+y | | 4b-3(3-4b)=7 | | 9(y-4)=5y-32 | | 5y-9+y+55=7y+50-3y | | 7a+3b=1 | | 3b+4=-7b+11 | | 7a-3b=1 | | Q=180-5p | | 9x-3+8x=2x+4-4x | | f(x)=5x^4+12x^3+-16x^2+10 | | 6.5w=-123.5 | | 9x-7x=36 | | -2x-2=50x-50 | | 6x+7x+9x=88 | | 10-3=x-9 | | R=F+460 | | 2x+y=1.25 | | 5x+2x=154 | | 6x+(-78)-30x=-6 | | 2x-8x+3x-7x= | | 15-7w=1 |